Extraction of naphthenic acids from acidic petroleum crude oil utilizing 2-methylimidazole with the aid of CA/AL2O3 and CE/AL2O3 catalysts / Emilysa Izani Mohd Fadzil - Mohd Fadzil, Emilysa Izani (2020)
Naphthenic Acids (NAs) found in crude oil is the major causes of corrosion problems in oil pipelines, distillation unit, storage, and fascilities. As a result, crude oil with high NA will be marketed at lower price and considered as low quality. In this study, catalytic extraction reaction was done in order to lowering the Total Acid Number (TAN) in crude oil to below than one mg KOH/g utilizing 2-methylimidazole with the aid of monometallic Ca/Al2O3 and Ce/Al2O3 catalysts. The catalyst was supported on the alumina beads by Incipient Wetness Impregnation (IWI) methods and calcined at calcination temperature of 700C. Thermogravimetry Analysis-Differential Thermal Analysis (TGA-DTA) was used to determine the suitable calcination temperature for both catalysts. Petronas Penapisan Melaka crude oil was selected to be tested with TAN of 5.30 mg KOH/g. The parameters studied were catalyst loading, and reaction times. The catalytic reaction was fixed at reaction temperature at 27C The result shows that Ca/Al2O3 and Ce/Al2O3 catalysts successfully reduced TAN value in acidic crude oil below than 1.00 mg KOH/g. Ca/Al2O3 catalyst gave a better reduction with 0.08 mg KOH/g of TAN value compared to Ce/Al2O3 catalyst which only reduced to 0.65 mg KOH/g of TAN value. Stretching modes of pure metal oxide (M=O) were detected before and after the reaction while CH3 stretching, carboxylic acid (C=O) and CH2 and CH3 bend was detected after the reaction which indicates that there were impurities has been adsorbed on both catalyst by FTIR analysis. As a conclusion, Ca/Al2O3 is the best catalyst compared to Ce/Al2O3 since it lowered down acid number in crude oil to lowest value than Ce/Al2O3 catalyst. The catalytic method of extraction technique successfully in extract NAs from the crude oil. Thus, reducing the TAN value to less than 1 mg KOH/g.